2007
DOI: 10.1016/j.ajo.2007.05.029
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Contact Lens Solution Use and Acanthamoeba Keratitis

Abstract: Purpose-Diagnosis of Acanthamoeba keratitis, a rare but serious corneal infection, has recently increased significantly at the University of Illinois at Chicago (UIC) Cornea Service. The purpose is to investigate Acanthamoeba keratitis risk factors.Design-Retrospective case-control study. Results-Thirty-nine (73.6%) cases and 113 (65.3%) controls participated; 38 cases had complete contact lens data. Thirty-five of 38 cases (92.1%) and 47 of 100 controls (47.0%) used soft lenses. Analysis was performed on 30 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 219 publications
(157 citation statements)
references
References 53 publications
3
152
0
2
Order By: Relevance
“…16 Previously published studies have also reported associations between certain multipurpose solution types and Fusarium and Acanthamoeba outbreaks of contact lens-related microbial keratitis. [25][26][27] Certain polymeric biguanide-based care solutions have been demonstrated to be less effective against bacterial biofilms in comparison with hydrogen peroxide or polyquaternium-based solutions. 28 In addition, reduction in microbial efficacy of this product has been reported when used for the storage of contact lenses in lens cases over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…16 Previously published studies have also reported associations between certain multipurpose solution types and Fusarium and Acanthamoeba outbreaks of contact lens-related microbial keratitis. [25][26][27] Certain polymeric biguanide-based care solutions have been demonstrated to be less effective against bacterial biofilms in comparison with hydrogen peroxide or polyquaternium-based solutions. 28 In addition, reduction in microbial efficacy of this product has been reported when used for the storage of contact lenses in lens cases over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Because none of the visual outcome prognostic factors have been reported or analyzed, those patients involved in previous analyses of geographic case distribution and contact solution use were not excluded. 7,8 Disease Definition and Data Collection AK was diagnosed as previously described; 7 in summary, diagnosis was based on clinical characteristics and identification of 1 or more of the following conditions: (1) identification of trophozoites or cysts on confocal microscopy; (2) identification of trophozoites or cysts through smears when specimens were stained with Diff-Quick stain; (3) positive Acanthamoeba cultures; or (4) pathologic identification of Acanthamoeba-like cysts on keratoplasty specimens. Corneal disease stage was evaluated by a single clinician (EYT) at presentation on the basis of clinically evident findings through slit-lamp biomicroscopy and categorized into 1 of 5 levels of progressive anatomic involvement and disease severity (epitheliitis, epitheliitis with radial neuritis, anterior stromal disease, deep stromal disease, or ring infiltrate) (Fig 1).…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this study is to identify prognostic factors for disease outcome and visual morbidity through analysis of a recent AK outbreak in the Chicago area. 7,8 …”
mentioning
confidence: 99%
“…3,37 The abrupt rise in cases, however, makes it unlikely that a radical change in hygiene habits was solely responsible and, further, the large number of cases not using AMO Complete MoisturePlus still constituted a sizable increase over the known background rate of infection making it also unlikely the sole cause. 37 Focus on other contemporaneously introduced risk factors including the labeling change for the use of multipurpose solutions allowing the omission of lens rubbing as well as the introduction and subsequent market dominance of silicone hydrogel lenses in the contact lens market have similarly not yielded an explanation. 3,11 The lack of a specific lens-related risk factor and the significant increase across all solution systems and lens types suggests an increase in exposure to Acanthamoebae characteristic of water contamination seen with almost all previous outbreaks.…”
Section: Recent Increases In Acanthamoeba Keratitismentioning
confidence: 99%
“…Several parasitic corneal pathogens have been well described, including Onchocerca, Leishmania, and Trypanosoma, 1,2 with recent attention focused on notable numbers of Microsporidia keratitis in South Asia and a more modest increase of Acanthamoeba keratitis in the United States as well as other developed countries. [3][4][5][6][7][8][9][10] Clinically, parasitic infections are usually characterized as chronic and intractable presenting with non-specific findings masquerading as other infectious and non-infectious disease. Despite the recent outbreaks, these infections remain comparatively rare, requiring a substantial clinical suspicion to warrant the specific media and/or special histological expertise for diagnosis.…”
Section: Introductionmentioning
confidence: 99%